2020
DOI: 10.3390/agronomy10040524
|View full text |Cite
|
Sign up to set email alerts
|

Potential Application of Crotalaria longirostrata Branch Extract to Reduce the Severity of Disease Caused by Fusarium

Abstract: Fusarium are considered as the major plant pathogen fungi, that cause the majority of soil-borne diseases to more than 100 plant species in the world, including maize. Thus, there are emerging demands of biocontrol reagents, and Crotalaria longirostrata showed fungicidal activity. The C. longirostrata branch extract was phytochemically characterized and evaluated for efficacy for the control of Fusarium wilt in maize. The application of the extract reduced the percentage of disease incidence significantly caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
(36 reference statements)
0
4
0
4
Order By: Relevance
“…Cruz-Rodríguez, et al [55] evaluated the C. longirostrata branch extract for the control of Fusarium wilt in maize. The…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cruz-Rodríguez, et al [55] evaluated the C. longirostrata branch extract for the control of Fusarium wilt in maize. The…”
Section: Discussionmentioning
confidence: 99%
“…Cruz-Rodríguez, et al [55] studied The C. longirostrata branch extract efficacy for the control of Fusarium wilt in maize. The application of the extract reduced the percentage of disease incidence significantly caused by Fusarium verticillioides from 70.4% to 40.12% as compared to non-treated plants, and the disease severity was reduced from 40.15% to 29.46%.…”
Section: Genetic Methods: Use Of Resistant Cultivarsmentioning
confidence: 99%
See 1 more Smart Citation
“…Las hojas son fuente de carotenoides, vitamina C, hierro, calcio y proteínas; además, se ha documentado la presencia de compuestos fenólicos, como flavonoides, saponinas, cumarinas, taninos, antraquinonas, antronas y alcaloides (Arias et al, 2003;Bibi et al, 2015;Cruz-Rodríguez et al, 2017). Además, existen estudios que demuestran mayor diversidad de usos; un caso es el de los extractos de sus tallos, ramas y raíces que inhiben el desarrollo del micelio y la esporulación de fitopatógenos y fitoparásitos como Fusarium sp., Aspergillus flavus Link (Cruz-Rodríguez et al, 2017;Miranda-Granados et al, 2018;Cruz-Rodríguez et al, 2020) y nematodos (Villar & Zavaleta-Mejía, 1990). Todas las estructuras de la planta se han evaluado en nuevas aplicación en herbolaria (Fischler & Wortmann, 1999;Arias et al, 2003;Basurto-Peña, 2011), como abono verde (Desaeger & Rao, 2000), forraje (Arias et al, 2003), alimento para el cultivo y multiplicación de tilapia nilótica (Oreachromis niloticus L.) (Guerra-Centeno et al, 2016) y caracoles de agua dulce (Pomacea flagellata Say) que son alimento, rico en proteína para humanos (Martínez, 2016).…”
Section: Introductionunclassified
“…Two articles investigated the use of plants or plant extracts as biocontrol agents. Cruz-Rodriguez et al [11] showed that the supplementation of branch extracts of Crotalaria longirostrata reduced the disease severity in maize upon Fusarium infection. The supplementation of dried spearmint and oregano increased tomato growth with respect to Fusarium and Verticillium infection [12].…”
mentioning
confidence: 99%